Pengaruh Kompetensi dan Kompensasi pada Masa Pandemi Covid-19 Terhadap Kinerja Karyawan di Puri Wulandari Hotel Ubud - I Putu Agus Suwastawa; I Dewa Agung Ayu Eka Idayanti; Anak Agung Istri Agung Ovy Dwijayanthi (Jurnal Riset Ekonomi dan Akuntansi, 2023)
Bali Province is one of the tourist destinations that is in demand by many tourists, both domestic and foreign. In addition to having a variety of interesting tourist and cultural objects, Bali also has many hotels with the best facilities in them. Hotel as one of the industries in the tourism sector is very dependent on the performance of human resources. The importance of human resources makes the company must have a strategy to improve employee performance. The high performance of employees can facilitate the company in achieving its goals. The purpose of this study was to analyze the Effect of Competence and Compensation in the Covid-19 Pandemic Period on Employee Performance at Puri Wulandari Hotel Ubud. This study used a sample of 120 respondents with a total sampling method. The data analysis technique used is descriptive analysis technique, classical assumption test, and multiple linear regression technique. The software used is SPSS 23. The results of this study indicate that competence has a positive and significant effect on employee performance. The higher the competence possessed, the higher the employee's performance. Compensation has a positive and significant effect on employee performance. The higher the compensation provided by the company, the higher the employee's performance. Competence and compensation have a positive and significant effect on competence and compensation together have a positive effect on employee performance.